2019
DOI: 10.1590/1980-5373-mr-2018-0623
|View full text |Cite
|
Sign up to set email alerts
|

F-127-Assisted Sol-Gel Synthesis of Gd2O3:Eu3+ Powders and Films

Abstract: In the current work, the influence of Pluronic F-127 (S = F-127) and temperature on the luminescent properties of Gd 2 O 3 :Eu 3+ (Gd:S = 1:2) powders and films was studied. In order to synthesize the powders and films (by the dip-coating technique), Gd 2 O 3 : Eu 3+ (5 mol%) ceramics were elaborated by the sol-gel route, using gadolinium and europium nitrates as precursors. The results obtained by means of X-ray diffraction, confirmed the presence of the cubic structure of Gd 2 O 3 (in 800 ºC heat-treated pow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 48 publications
0
2
0
1
Order By: Relevance
“…2a. Via applying the following equations [43], where D (nm) is the size of the nanocrystal administration sample, (nm) is the wavelength, and is the molar absorptivity of the first excitonic absorption peak of the corresponding sample. The used molar concentration of the D = 1.6122 × 10 −9 4 − 2.6575 × 10 −6 3 + 1.6242 × 10 −3 2 − (0.4277) + (41.57) = 5857(D) 2.65 synthesized CdS QDs was 6.6 × 10 -6 M and the CdS QDs size was 3-6 nm.…”
Section: Resultsmentioning
confidence: 99%
“…2a. Via applying the following equations [43], where D (nm) is the size of the nanocrystal administration sample, (nm) is the wavelength, and is the molar absorptivity of the first excitonic absorption peak of the corresponding sample. The used molar concentration of the D = 1.6122 × 10 −9 4 − 2.6575 × 10 −6 3 + 1.6242 × 10 −3 2 − (0.4277) + (41.57) = 5857(D) 2.65 synthesized CdS QDs was 6.6 × 10 -6 M and the CdS QDs size was 3-6 nm.…”
Section: Resultsmentioning
confidence: 99%
“…[10,23] By comparing the luminescence properties of the sol-gel-prepared Gd 2 O 3 :Eu 3+ film and powder, Murillo et al found that the film has a higher efficiency for energy translation from host to dopant, which means that the film would be more suitable than the powder as a luminescent material. [60] The disadvantages of films are low brightness and luminescence effectiveness relative to their correspondent powder phosphors. The structural characteristics and thickness of films are profusely connected to their luminescence efficiency.…”
Section: Correlation Between the Structural Transformation And Lumine...mentioning
confidence: 99%
“…Pode ser incorporado em diferentes matrizes hospedeiras em que há uma eficiente transferência de energia entre a matriz e este íon 111,112 . Estudos mostram a dopagem de Eu 3+ em matrizes como o Y2O3 [113][114][115] , NaGdF4 116,117 , Sr2CeO4 118 e Gd2O3 [119][120][121] .…”
Section: Downconversion E Upconversionunclassified